Congenital laryngeal anomalies in childhood - Yulia E. Stepanova (Consilium Medicum)
Background. Diagnosis of congenital malformations of the larynx in children is a difficult task for otorhinolaryngologists. The development and implementation of video endoscopic techniques has made a significant contribution to the understanding of anatomical changes in the larynx during CPR.